Africa RISING Baseline Evaluation Survey (ARBES) report for Tanzania - Charles, A.; Azzarri, Carlo; Haile, Beliyou; Comanescu, M.; Roberts, C.; Signorelli, S. (International Food Policy Research Institute, 2016)
This report presents overall summaries and cross-tabulations, and empirical means-difference tests across household type, location, wealth, and gender of head, for data that cover 810 households in Africa RISING areas in northern and north-central Tanzania in three districts (Babati, Kiteto and Kongwa) and twenty-five villages in which Africa RISING was either operational or pre-operational at the date of the survey (February-April 2014). Following a description of the report and of the survey from which its data are drawn, its main findings are presented in two parts, providing description and analysis of household- and community-level data, and these also include a series of tables and graphs to further illustrate the descriptive results. Each part contains six sections. For household-level data, these include household demographics, health and nutrition, dwelling characteristics and asset ownership, agriculture, household consumption, and shocks and vulnerability. And for community-level data, these cover community demographics, access to services, extension advice and farmer groups, land and major crops, shocks, and food prices.